Characteristics of pointing actions of top level female competitors in karate - Koropanovski, N.; Jovanovic, S.; Dopsaj, M. (World Congress of Performance Analysis of Sport VIII, 2008)
The obtained results indicate certain specificities of sports fight in females in comparison with men (Koropanovski and Jovanovic, 2007). Dominantly prevailing are punches with 95.91%, compared to kicks with 3.1%. Regardless of changes in rules which favor kicks by assigning more points to them, punches possess smaller informational complexity - programming duration, and greater preciseness, control and characteristics of natural movements. Besides mentioned, kicks are less demanding from the aspect of oxygen uptake (VO2) and heart rate (Imamura, H et al., 2002). On the other hand, having in mind that only the final matches were analyzed, it is quite possible that female competitors were trying to minimize the risk. The punch gyaku zuki is the most prevailing with the total of 85.57%. This punch possesses the shortest duration of programming, it is very powerful and precise, and therefore it`s suitable for most competition operations. Besides, when performing it, female competitor stays protected, which contributes to additional safety. The punch oi zuki is on the third place, considering its frequency. It is widely known that this punch is performed using full step. With careful analysis it was determined that female competitors were performing this punch from no greater distance than that in case of gyaku zuki punch, but they used their determination to force the opponent to move backwards, in that way achieving the optimal distance for pointing. Frequency of occurrence of modalities of pointing ways can be generalized in the following way: pointing from attack 47.54%, pointing from counterattack 9.9% and pointing from interception 42.57%. Great frequency of pointing from interception can be explained with the fact that women are adjusting very slowly to current judging rules, given that interception was evaluated with maximum pointing scores earlier. Also, shorter duration of fight and fewer number of points one can achieve in women`s competition are additional reasons for great prevalence of pointing from interception, which is the least risky way of pointing.